Advancements in Ostrowski type fractional Integral Inequalities via Applications of Jensen's and Young's Inequalities (European Journal of Pure and Applied Mathematics, 2025)
Fractional integral operators and convexity have a close link due to their fascinating properties in the mathematical sciences.In this paper, we first establish an integral identity involving the generalized Hattaf-fractional integral operators. By using the Jensen integral inequality, Young's inequality, power-mean inequality, and Hölder inequality, we then apply this identity to provide some new generalizations of Ostrowski type inequality for the convexity of $|\aleph|$. Furthermore, we deduce several special cases from the main results. The results of this novel investigation should lead to new discoveries in the area of fractional calculus and inequalities.